Cross-Country Comparison of Bans on Internet Tobacco Advertising, and Search Interest in Vaping Products. - Ramadan, Majed; Alsiary, Rawiah A; Aboalola, Doaa A.; Aouabdi, Sihem (Tobacco Use Insights, 2025)
Background: The rise in vaping use across high-income countries is driven partly by marketing, advertising, and flavors promoted by e-cigarette producer firms. The current study aim is to examine the potential variation in the relative research volume on vaping products between countries with highest level of tobacco banning internet advertising and those with no ban on tobacco internet advertising. Method: We used weekly relative search volume (RSV) data produced by Google Trends (GT). A total of eight countries included in the study, Saudi Arabia, United Arab Emirates, United States, Ireland, New Zealand, Canada, United Kingdom, and Australia. The countries were regrouped into ban in internet advertising countries, and the no bans in internet advertising countries. Results: The trend test indicates a statistically significant upward trend in GT vaping search volume across all the included countries. However, the percentage increase of search volume for the ads no ban group was higher than ban group. There is a statistically significant difference in median between the two group, (P < 0.0007), (median, 6.25 [IQR, 0.103] for the ban in internet advertising countries vs (median 7.5 Interquartile Ranges (IQR), [0.542] for the no bans on internet advertising countries. Conclusion: Countries with stringent bans on online tobacco advertising have shown lower levels of vaping-related search interest, indicating the potential effectiveness of such regulations. Our research underscores the importance of emphasizing comprehensive bans on tobacco advertising and sales online could help mitigate the upward trend in vaping interest.